Neuromarketing a New Tool for Marketing Research - R. Ganesh (International Journal of Optical Innovations & Research, 2024)
In recent years, a new marketing research tool called neuromarketing has emerged that uses brain research in a management context and has become popular in curricula and the world of practice. Neural Production caught the attention of publishers in early 2002 by making the publisher's job easier by simplifying the way and process of searching for ideas. This article examines the role of neuromarketing theory as a useful tool for marketers in the new era of marketing research for today's buyers. The brain's reaction as determined by these methods might not always be reliable for the individual. For that reason, focus groups, polls, and other methods may be used to get this data. Reports other than personal can be submitted through many channels. The aim of our research focuses on the following: Neuromarketing and neuroimaging included in the current situation, electroencephalography, functional magnetic resonance imaging, eye tracking, etc. applications. Paper Measure Consumer Dialectics the consumer contradicts himself, says what he wants but does what he wants – market research now focuses on the use of neuromarketing practices on four aspects of the consumer: body, mind, soul, and spirit.
Keywords: EEG; FMRI; Neuromarketing-NM; brain research; eye tracking; neuroimaging; zaltman metaphor induction technology-ZMET